Relações de interesse público e o privado: o trabalho precário nas organizações sociais de saúde no contexto da governamentalidade neoliberal - Salles, Shayene Machado (2017)
The aim is to investigate the expansionism of precarious labor in Brazil, especially in relation to Health Social Organizations, private non-profit entities that constitute the sector named “non-state public sphere”, responsible for providing health services and for the private management of public resources. We sought to question how the neoliberal governmental rationality operates in creating flexible and precarious labor relations in the Health Social Organizations. Having as a theoretical basis Foucault’s category of “neoliberal governmentality”, we situated the precariousness and flexibility of the labor relations that develop in the Health Social Organizations as a product of a governmental rationality oriented by market principles, whose political and institutional mark had its peak in the 1990s, with the Public Management Reform, articulated and influenced by the economist Luiz Carlos Bresser-Pereira. This research has the objectives of: a) analyzing the precariousness of labor relations that develop inside the Health Social Organizations, having the neoliberal governmentality, an analytical category created by Michel Foucault, as a starting point; b) articulating constitutive elements of this governmental rationality that allow us to confront the application of its rationality with the implementation of practices and policies that stimulate precarious labor; c) contextualizing legal interventionism in the market economy through the analysis of legislative proposal (PL nº 4330/204) and judicial decision (ADIn nº 1923/1998) that corroborate the adoption of practices of labor precariousness stimulation in the health sector, and, consequently, in the Health Social Organizations. The articulation of constitutive elements of the structuring category of this research has allowed for seeing the laborer as a human capital and the Law as a field of intervention in the economy – both being results of the indexation of government and society by the business model. From applying the theory of the human capital to the notes that suggest a biopolitical intervention in the life of the laborer, we analyzed how human labor is established in the point of view of a market rationality of government, weakening this laborer with its precariousness and flexibilization, compromising substantially the exercise and effectiveness of this fundamental right.